Protein Identification of Spermatozoa and Seminal Plasma in Bottlenose Dolphin (Tursiops truncatus) - Fuentes-Albero, Mari-Carmen; González-Brusi, Leopoldo; Cots, Paula; Luongo, Chiara; Abril-Sánchez, Silvia; Ros-Santaella, José Luis; Pintus, Eliana; Ruiz-Díaz, Sara; Barros-García, Carlos; Sánchez-Calabuig, María-Jesús; García-Párraga, Daniel; Avilés, Manuel; et al. (Frontiers in Cell and Developmental Biology, 2021)
Proteins play an important role in many reproductive functions such as sperm maturation and physiology, sperm transit in the female genital tract or sperm-oocyte interaction. However, in general, little information concerning reproductive features is available in the case of aquatic animals. The present study aims to characterize the proteome of both spermatozoa and seminal plasma of bottlenose dolphins (Tursiops truncatus) as a model organism for cetaceans. Ejaculate samples were obtained voluntarily from two trained dolphins housed in an aquarium. Spermatozoa and seminal plasma were analyzed by means of proteomic analyses using an LC-MS/MS, and a list with the gene symbols corresponding to each protein was submitted to the DAVID database. Of the 423 proteins identified in spermatozoa and 307 in seminal plasma, 111 proteins were shared by both. Furthermore, 70 proteins were identified as involved in reproductive processes, 39 in spermatozoa, and 31 in seminal plasma. The five most abundant proteins were also identified in these samples: AKAP3, ODF2, TUBB, GST3, ROPN1 for spermatozoa and CST11, LTF, ALB, HSP90B1, PIGR for seminal plasma. In conclusion, this proteomic study provides the first characterization of proteomic expression patterns in cetacean sperm and seminal plasma, opening the way to future research into new biomarkers, the analysis of conservation capacity or possible additional applications in the field of assisted reproduction technologies.